Wearable, wireless gas sensors using highly stretchable and transparent structures of nanowires and graphene. Issue 20 (11th May 2016) - Park, Jihun; Kim, Joohee; Kim, Kukjoo; Kim, So-Yun; Cheong, Woon Hyung; Park, Kyeongmin; Song, Joo Hyeb; Namgoong, GyeongHo; Kim, Jae Joon; Heo, Jaeyeong; Bien, Franklin; Park, Jang-Ung
Abstract : Wearable, wireless gas sensors based on silver nanowire (AgNW)–graphene hybrid nanostructures provide superb real-time sensing performances and mechanical robustness. Abstract : Herein, we report the fabrication of a highly stretchable, transparent gas sensor based on silver nanowire–graphene hybrid nanostructures. Due to its superb mechanical and optical characteristics, the fabricated sensor demonstrates outstanding and stable performances even under extreme mechanical deformation (stable until 20% of strain). The integration of a Bluetooth system or an inductive antenna enables the wireless operation of the sensor. In addition, the mechanical robustness of the materials allows the device to be transferred onto various nonplanar substrates, including a watch, a bicycle light, and the leaves of live plants, thereby achieving next-generation sensing electronics for the 'Internet of Things' area.